Epidemiological profile of notifications of gestational and congenital syphilis in Alagoas (2018–2024) (Research, Society and Development, 2026)
This study analyzed the epidemiological profile of gestational and congenital syphilis notifications in the state of Alagoas between 2018 and 2024. Secondary data from the Information System for Notifiable Diseases (SINAN/DATASUS) were analyzed descriptively, calculating absolute frequencies and percentage variations. In 2018, 953 cases of gestational syphilis and 450 cases of congenital syphilis were reported, while in 2024, these numbers decreased to 483 and 213 cases, representing reductions of 49.3% and 52.7%, respectively. Despite this decline, the figures remain above the World Health Organization target for congenital syphilis elimination, which is less than 0.5 cases per 1,000 live births. The observed reduction may reflect advances in rapid testing, professional training, and partner treatment, but socioeconomic factors and health crises, such as the COVID-19 pandemic, may have limited the results. These findings highlight the need to maintain and strengthen public policies, prenatal care, early screening, and health education to achieve the elimination of congenital syphilis in Alagoas.